ADVERSE EFFECTS OF ANTIEPILEPTIC DRUGS - I. Yu. Kovaleva (Эпилепсия и пароксизмальные состояния, 2017)
Antiepileptic drugs are frequently associated with a risk of adverse effects,  which have an impact on the tolerability and success of treatment. Patients who develop intolerable adverse effects have to discontinue treatment early after initiation or to switch to another antiepileptic drug. A long-term management  strategy for the patients with such a long-lasting chronic disease  as epilepsy should include both effective  seizure control and early detection  of adverse drug events, ensuring prognosis, prevention and minimizing side effects,  which is quite important. All these measures  are expected to improve adherence to treatment, quality of patients’ life and control of epilepsy.